2018
DOI: 10.18176/jiaci.0243
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Anaphylaxis Guidelines: Real-World Data From the Emergency Department of a Tertiary Hospital

Abstract: Background:To date, few studies have evaluated the degree of compliance with recommendations of anaphylaxis guidelines in emergency departments (EDs). Objective: The objective of this study was to evaluate adherence to anaphylaxis guidelines recommendations in an ED of a tertiary hospital. Methods: Medical records of patients that were assisted in the ED of the University Hospital of Salamanca (Spain) were reviewed. Those patients fulfilling anaphylaxis criteria proposed by the NIAID/FAAN were selected. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(48 reference statements)
2
5
1
Order By: Relevance
“…This study shows that anaphylaxisoccurs across all age groups. As observed in other case-series,a predominance of anaphylaxis was found in female gender in adults, whereas in children there was a male predominance [5,13,15,16,19,20].It has been suggested that endocrine factors might be involved in the pathogenesis of this disease, as with other immune-based diseases [5,19]. Food allergywas the main elicitor of anaphylaxis, as it has been described in several case-series, especially when children are included [8,11,13,15,16,[20][21][22][23].Shellfish and CM were the main culprits, in adults and in children, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This study shows that anaphylaxisoccurs across all age groups. As observed in other case-series,a predominance of anaphylaxis was found in female gender in adults, whereas in children there was a male predominance [5,13,15,16,19,20].It has been suggested that endocrine factors might be involved in the pathogenesis of this disease, as with other immune-based diseases [5,19]. Food allergywas the main elicitor of anaphylaxis, as it has been described in several case-series, especially when children are included [8,11,13,15,16,[20][21][22][23].Shellfish and CM were the main culprits, in adults and in children, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…As observed in other case-series,a predominance of anaphylaxis was found in female gender in adults, whereas in children there was a male predominance [5,13,15,16,19,20].It has been suggested that endocrine factors might be involved in the pathogenesis of this disease, as with other immune-based diseases [5,19]. Food allergywas the main elicitor of anaphylaxis, as it has been described in several case-series, especially when children are included [8,11,13,15,16,[20][21][22][23].Shellfish and CM were the main culprits, in adults and in children, respectively. CM was the leading cause in children, as reported by others [6,15,16,18,21],especially in the first years of life [6,15].These findingsdiverge from those of other authors [8,14,[23][24][25],underlining the importance of having a detailed knowledge of each country's reality.The observed frequency has variations, based on the studied age group, the geographical region and the associated food habits [6,13,14,24,26].Other main foods in this study were fresh fruits and TNs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Proportionally fewer patients correctly received injectable promethazine and corticosteroids (oral or intravenous) and more patients with anaphylaxis received adrenaline and an adrenaline autoinjector on discharge. Where comparisons could be made, these results are better than those reported in recent studies …”
Section: Projectscontrasting
confidence: 51%
“…The plan includes the indication to attend the ED for follow-up or further treatment. Patients and caregivers do not always adhere to their plan [14][15][16]. Allergists are confident that patients with anaphylaxis are attended immediately in the ED.…”
Section: Discussionmentioning
confidence: 99%